The Influence of Organizational Climate and Self-Esteem on Job Satisfaction of Civil Servants at the Office of Public Housing, Settlement Areas, and Environment of Ketapang Regency - Lestari, Kenanga Bunga; Mahdi, Irfan (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to examine the influence of organizational climate and self-esteem on the job satisfaction of civil servants at the Office of Public Housing, Settlement Areas and Environment of Ketapang Regency. A quantitative approach with an associative design was applied. The population consisted of 69 civil servants, all of whom were included as respondents through a census sampling technique. Primary data were obtained from interviews with the Office Secretary and through Likert-scale questionnaires, while secondary data were collected from staffing records, attendance reports, disciplinary documents and performance evaluations. The research instrument was assessed through validity and reliability testing, and the data were analyzed using multiple linear regression to identify partial and simultaneous effects. The results indicate that organizational climate and self-esteem both have a positive and significant effect on job satisfaction. The coefficient of determination shows that these two variables explain 46.7% of the variation in job satisfaction, while the remainder is influenced by factors outside the model. The findings highlight the importance of work environment conditions and internal psychological states as key determinants of job satisfaction in public organizations. Practically, the institution is encouraged to strengthen its organizational climate and enhance employees’ self-confidence through development and empowerment programs. Future studies may incorporate additional variables such as work motivation, workload, leadership style or work-life balance, or expand the research setting to provide a broader understanding of the factors influencing job satisfaction in government institutions.